Neighbourhood Contexts and Low Birthweight: Social Disconnection Heightens Single Parents Risks in Saskatoon - Muhajarine, Nazeem (Can J Public Health, 2009)
BACKGROUND: The majority of research to date on low birthweight (LBW) has emphasized maternal characteristics, and less so how maternal risk is shaped (via contextual factors). This study aims to understand how neighbourhood characteristics influence LBW, independently and in interaction with individual factors, in the context of community-defined neighbourhoods. METHOD: All singleton births for a 3-year period (1992-1995; n=8504) to mothers resident in Saskatoon comprised the study population. Data included were child and mother’s/father’s characteristics and six neighbourhood characteristics: socio-economic disadvantage, social disconnection, physical condition, population density, availability and accessibility of local programs and services, and smoking prevalence. Multilevel modeling for a binary outcome (LBW) was employed; odds ratios and 95% confidence intervals for the final model were reported. RESULTS: Newborns in families receiving income assistance, with a mother over 40, and whose mother had previous stillbirths were at greater risk for LBW; however, mothers who had more than one previous live birth were less likely to have a LBW baby. Independent of individual-level risk factors, infants in socio-economically disadvantaged neighbourhoods were at increased risk for LBW (OR 1.34; 95% CI 1.07, 1.68). Most interestingly, the risk of LBW among infants born to single mothers was exacerbated by greater level of neighbourhood social disconnection. Neighbourhoods with low levels of social disconnection have a lower risk of LBW among single mothers (OR=0.89, 95% CI 0.72, 1.17) compared to those with high levels (OR=1.57, 95% CI 1.18, 1.93). CONCLUSION: Neighbourhood contextual factors influence the risk of LBW directly, via independent effects, as well as through moderating the risk of individual factors. Studies that simultaneously examine both individual and contextual effects on LBW could provide a stronger evidentiary base for multiple points of interventions targeting individuals as well as settings.